Steroid induced psychiatric adverse effects: an overview of risk factors, clinical features and management - Parasher, Anant; Bez, Jeplin (International Journal of Research in Medical Sciences, 2020)
Corticosteroids have been in use since the past five decades as anti-inflammatory and immunosuppressive drugs for the treatment of several pathologies such as asthma, allergy, rheumatoid arthritis, and dermatological disorders. Adverse effects include growth retardation in children, immunosuppression, hypertension, hyperglycemia, inhibition of wound repair, osteoporosis, metabolic disturbances, glaucoma, and cataracts. The psychiatric effects of steroids are due to the wide expression of Glucocorticoid Receptors in the brain, and their long-term modulation can lead to functional and anatomical alterations along with hippocampal dysfunction. In most cases, the psychiatric symptoms disappear on cessation of steroid therapy; others may require some form of therapeutic management. A search was conducted for clinically relevant articles from 1971 to 2016 by including the terms corticosteroids, mania, depression, psychosis and cognitive defects. About one-fifth of patients receiving high doses of corticosteroids develop psychiatric symptoms. These symptoms are observed to be dose-dependent and generally occur during the first few weeks of therapy. Lithium has a preventive as well as therapeutic role, while antipsychotics are reserved for high risk cases with predominant psychotic symptoms. Psychiatric effects of long term steroid therapy have become increasingly common nowadays due to long duration of treatment of many chronic respiratory and orthopedic illnesses. Reduction in the dose or complete discontinuation of steroid therapy has been proven beneficial in many patients. Among the therapeutic options, lithium has a definitive role, both in the prevention as well as treatment of psychiatric symptoms. Better co-ordination between the physician and psychiatrist can go a long way to improve the quality of life in these patients.